2015
DOI: 10.1007/978-3-662-48319-0_35
|View full text |Cite
|
Sign up to set email alerts
|

Negativity Bias Effect in Helpfulness Perception of Word-of-Mouths: the Influence of Concreteness and Emotion

Abstract: Abstract. Word-of-mouth (WOM) is a powerful information resource for consumers to judge a product or service. WOM has persuasive power when audiences regard it as helpful. There is a psychological phenomenon, called the negativity bias, in which negative WOMs are usually regarded as more helpful than positive ones. However, not all previous studies supported the existence of negativity bias. This paper examines the negativity bias effect of WOM and explores the moderating effect of length and emotional content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…The literature also suggests that consumers tend to find concrete information more useful as it promotes customer satisfaction (Packard & Berger, 2017, 2020; Thomas, 2020) in that less concrete language leads to greater skepticism (Backof et al, 2016; Nolder & Kadous, 2018; Rasso, 2015). Importantly, Wang et al (2015) showed that consumers found negative information more concrete and helpful. Building on this body of research, we argue that since consumers use reviews to reduce their uncertainty about a product, more factual (objective/concrete) review content would be considered useful as it would inform the purchase decision more so than nonfactual (subjective/abstract) information.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…The literature also suggests that consumers tend to find concrete information more useful as it promotes customer satisfaction (Packard & Berger, 2017, 2020; Thomas, 2020) in that less concrete language leads to greater skepticism (Backof et al, 2016; Nolder & Kadous, 2018; Rasso, 2015). Importantly, Wang et al (2015) showed that consumers found negative information more concrete and helpful. Building on this body of research, we argue that since consumers use reviews to reduce their uncertainty about a product, more factual (objective/concrete) review content would be considered useful as it would inform the purchase decision more so than nonfactual (subjective/abstract) information.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Prior work on online WOM has shown that its impact or persuasiveness depends on factors such as the characteristics of the reviewer (e.g., Godes and Mayzlin 2009) and the characteristics of the review itself, such as its linguistic characteristics (e.g., Schellekens, Verlegh, and Smidts 2010). While some of these findings would imply that smartphonegenerated WOM might be less impactful or persuasive than PC-generated content (e.g., Banerjee and Chua 2014;Wang et al 2015), other findings suggest that smartphonegenerated content would actually be more impactful. For example, Ludwig et al (2013) find that increasing the proportion of positive emotional language in Amazon reviews led to higher customer conversion rates.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%